Posterior Chordae Rupture of the Tricuspid Valve due to Myocardial Infarction: A Rare Entity Among Tricuspid Valve Pathologies - Balla, Endri; Karslıoğlu, Arif Okay; Seri, Zoukou Marie France Dominique; Akpınar, Denizhan; Yamaç, Ecem Tuğba; Mansımzada, Elshad; Akay, Hakkı Tankut; Kesimci, Elvin; Sezgin , Atila (Brazilian Journal of Case Reports, 2025)
The tricuspid valve is rarely affected by myocardial infarction. The right ventricle has a lower systolic pressure compared to the left ventricle making the papillary muscles of the tricuspid valve more resistant to ischemia. The right coronary artery is the main blood supply to tricuspid papillary muscles, chordae rupture of the tricuspid valve may occur following myocardial infarction. Here, we present a rare case of a 70-year-old male with severe tricuspid regurgitation, a completely occluded right coronary artery (RCA), 70% stenosis of the left main coronary artery (LMCA), and 100% occlusion of the left anterior descending artery (LAD). The patient’s ejection fraction (EF) was reduced to 30%. Treatment included tricuspid valve repair using the bicuspidization technique and a five-vessel coronary artery bypass graft (CABG). This case demonstrates that, although rare, myocardial infarction can involve the tricuspid valve and that the surgery of the valve with full revascularization proved to be an effective treatment strategy in our patient.